2012
DOI: 10.4103/0300-1652.103551
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial myxoma as a possible cause of hemorrhagic stroke and sudden death

Abstract: Right atrial myxomas are rare primary tumors of the heart. They may remain asymptomatic or eventually cause constitutional signs and symptoms. Less frequently, obstruction of the tricuspid valve occurs, resulting in exertional dyspnea, syncope, or sudden death. Neurological manifestation as initial presentation of atrial myxomas is rarely, if ever, associated with right atrial myxomas and may be secondary to cerebral infarction, cerebral hemorrhage and, more rarely subarachnoid hemorrhage. We review the case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…These cardiovascular symptoms come from mitral valve obstruction and/or elevated left atrial pressure and include chest pain, dyspnea on exertion, orthopnea, and paroxysmal nocturnal dyspnea. 11 , 25 - 27 Other significant manifestations are neurological deficits from embolization of the myxoma, leading to events related to cerebral ischemia or infarction, 27 , 28 retinal artery occlusion, 29 and even sudden death. 21 However, patients can also present asymptomatically or with minimal cardiac symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These cardiovascular symptoms come from mitral valve obstruction and/or elevated left atrial pressure and include chest pain, dyspnea on exertion, orthopnea, and paroxysmal nocturnal dyspnea. 11 , 25 - 27 Other significant manifestations are neurological deficits from embolization of the myxoma, leading to events related to cerebral ischemia or infarction, 27 , 28 retinal artery occlusion, 29 and even sudden death. 21 However, patients can also present asymptomatically or with minimal cardiac symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although atrial myxomas are often found in the left atrium, they can occur in the ventricles in a small proportion of people (1,3). Most atrial myxomas begin to produce symptoms when they become sufficiently large.…”
Section: Discussionmentioning
confidence: 99%
“…Interference with mitral flow mimics mitral stenosis, as in our patient, with massively dilated left atrium, pulmonary hypertension and chronic heart failure that progress over an appreciable duration of time (2,3). Other constitutional symptoms of atrial myxomas include fever, weight loss, digital clubbing, reduced platelet count, elevated erythrocyte sedimentation rate and abnormal serum proteins (3,4,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the presence of an intracardiac shunt they can also be caused by a right-sided myxoma. Pulmonary embolism may originate from a right-sided myxoma 12 13…”
Section: Discussionmentioning
confidence: 99%